2020
DOI: 10.3390/cancers12123832
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Surveillance for Metachronous Esophageal Squamous Cell Neoplasms among Head and Neck Cancer Patients

Abstract: Esophageal squamous cell neoplasms (ESCNs) are the most common second primary neoplasm in patients with head and neck squamous cell carcinoma (HNSCC), and few studies have focused on metachronous ESCNs. We aimed to evaluate the incidence of and risk factors for metachronous ESCNs and to provide a reasonable endoscopic follow-up plan for HNSCC patients. We extended our prospective cohort since October 2008 by recruiting incident HNSCC patients. All enrolled patients were interviewed to collect information on su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…In our series, the overall 1-, 3-, and 5-year survival rates were 87.2 %, 68.1 %, and 58.59%, respectively. In a 10-year endoscopic surveillance cohort, HNSCC patients without dysplasia had the best survival rate compared to LGD and HGD or SCC (72.3 % vs 54.9 % vs 32.4 %, P < .0001) [19]. Notably, in the present series, the survival curves were similar between the patients without ESCC versus those with ESCC detected at an early stage, while the patients with advanced ESCC had a significantly worse prognosis, with an estimated 5-year survival probability of only 11.4 %.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our series, the overall 1-, 3-, and 5-year survival rates were 87.2 %, 68.1 %, and 58.59%, respectively. In a 10-year endoscopic surveillance cohort, HNSCC patients without dysplasia had the best survival rate compared to LGD and HGD or SCC (72.3 % vs 54.9 % vs 32.4 %, P < .0001) [19]. Notably, in the present series, the survival curves were similar between the patients without ESCC versus those with ESCC detected at an early stage, while the patients with advanced ESCC had a significantly worse prognosis, with an estimated 5-year survival probability of only 11.4 %.…”
Section: Discussionmentioning
confidence: 95%
“…Prospective studies have reported ESCC prevalence rates of 5.1 % to 12.5 % among patients with HNSCC, with differences attributed to both geographical variation and the location of the primary head and neck tumor 6 15 16 17 18 19 . These rates are higher than the estimated prevalence of 0.74 % in the general population 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, synchronous SPEC is defined as another cancer diagnosed within 6 months after detection of the first primary oral cancer, as frequently defined in previous studies. [18][19][20] The date of the first endoscopic examination within that time frame was defined as the index date for the screened group. Given that nonscreened patients lacked specific endoscopic screening dates, we randomly assigned a pseudo index date based on the dynamic frequency distribution of the interval between entry date and time exposure to the endoscopic examination from the screened group.…”
Section: Study Samplementioning
confidence: 99%
“…[15][16][17] One hospital-based study in Taiwan suggested that patients were encouraged to undergo endoscopic screening in the first 3 years after HNC diagnosis. 18 A review study moderately recommended endoscopic screening every 6-12 months for 10 years. 9 However, most literature and guidelines recommend regular endoscopic screening for patients with HNC in general, especially those with hypopharyngeal and oropharyngeal cancer, because of higher SPEC reveal rates among these patients than among those with oral cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation